Current trends in teaching a foreign language in the digital era - Tatiana A. Dmitrenko; Azat A. Akhmadullin (Training, Language and Culture, 2023)
In the digital era, a new concept of teaching foreign languages using digital technologies has been developed. Today’s emphasis is on cultivating highly competitive specialists who not only possess fluency in their respective professions to meet global standards but are also prepared to actively leverage digital technologies. The purpose of the article is to reveal current trends in teaching a foreign language in the digital era and to assess the opportunities and main ways to improve foreign language training for future specialists in the field of intercultural contacts, since the digitalisation of education has brought foreign language teaching to a qualitatively new level. The article explores the methodological foundations underpinning the concept of foreign language training for a competitive specialist through the integration of digital technologies. Employing analytical-synthetic methods, the comparative approach, and contrastive analysis of national and foreign educational practices, the study looks into the aspects of language training in the contemporary context. The authors reveal the content of the concepts ‘digital educational environment’, ‘digital technologies’ and ‘digital educational resources’ and identify problematic aspects of modern professional training for a foreign language teacher in the context of digitalisation of education. The identification of the most prominent trends in modern foreign language education was a key focus. The imperative shift towards utilising digital tools in language instruction was underscored, affirming their role in attaining high-quality outcomes in the training of competitive specialists. The article’s scientific novelty and theoretical significance stem from the authors’ rationale for incorporating digital technologies and establishing a digital learning environment in foreign language instruction. This entails not only an optimal blend of promising technologies but also the utilisation of a comprehensive array of tools and software. These tools enable the development of more advanced educational materials and foster foreign language speech activity among students through immersion in a dynamic digital language environment.